2018
DOI: 10.1016/j.cgh.2018.05.049
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Treatment of Rumination Syndrome

Abstract: Rumination syndrome is a functional gastrointestinal disorder characterized by effortless postprandial regurgitation. The disorder appears uncommon, although only limited epidemiologic data are available. Awareness of the characteristic symptoms is essential for recognizing the disorder, and thus avoiding the long delay in diagnosis, that many patients experience. Although objective testing by postprandial esophageal high-resolution impedance manometry is available in select referral centers, a clinical diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
54
0
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 43 publications
0
54
0
14
Order By: Relevance
“…Study proposed the Response Style Theory of Depression, which showed that people who are ruminating have the tendency to experience more negative emotions [21]. Hence, rumination scores should re ect the students' emotional state after failing the exam.…”
Section: Discussionmentioning
confidence: 99%
“…Study proposed the Response Style Theory of Depression, which showed that people who are ruminating have the tendency to experience more negative emotions [21]. Hence, rumination scores should re ect the students' emotional state after failing the exam.…”
Section: Discussionmentioning
confidence: 99%
“…Although the underlying pathogenesis remains unclear, the regurgitation of ingested material occurs because of a combination of increased intraabdominal pressure and negative intrathoracic pressure. 11 The diagnosis of rumination syndrome should be made clinically, using the Rome IV criteria. 11 The Rome IV criteria for rumination syndrome require persistent or recurrent regurgitation of recently ingested food into the mouth with subsequent spitting or remastication and swallowing and regurgitation not preceded by retching.…”
Section: Discussionmentioning
confidence: 99%
“…11 The diagnosis of rumination syndrome should be made clinically, using the Rome IV criteria. 11 The Rome IV criteria for rumination syndrome require persistent or recurrent regurgitation of recently ingested food into the mouth with subsequent spitting or remastication and swallowing and regurgitation not preceded by retching. 12 High-resolution esophageal manometry with postprandial protocol can be used to support the diagnosis, but the lack of its widespread availability and standardized protocols limit its generalizability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations